Binding site stoichiometry and the effects of phosphorylation on human α1 homomeric glycine receptors - Gentet, Luc J (Blackwell Science Inc, 2002)
The kinetic properties of the human α1 homomeric glycine receptor were investigated. Receptors were expressed in HEK 293 cells, and glycine was applied to outside-out membrane patches with sub-millisecond solution exchange. The activation time course of the glycine response was used to investigate receptor stoichiometry. The unbinding of three strychnine molecules and the cooperative binding of two glycine molecules were required to activate the channel. The effects of phosphorylation on glycine receptor kinetics were investigated by pretreating cells with phosphorylators or with phosphatases. Phosphorylation accelerated desensitisation, but slowed deactivation and recovery from desensitisation. A chemical-kinetic model was developed that reproduced the experimental observations. The model suggests that only three binding sites on the glycine channel are functional, while the remaining two binding sites are ‘silent’, possibly due to strong negative cooperativity.